Distribution of Nitrate Household Waste and Groundwater Flow Direction around Code River, Yogyakarta, Indonesia - Muryanto Muryanto; Suntoro Suntoro; Totok Gunawan; Prabang Setyono; Afid Nurkholis; Nurisa Fajri Wijayanti (Faculty of Geography, Universitas Gadjah Mada, 2019)
The nitrate concentrations in shallow groundwater of the Yogyakarta City and its surroundings has increased to about twenty times in the period 1985-2018. The objective of this study was to analyse the distribution of nitrate concentrations in water well around the Code River, Yogyakarta. Flownets mapping was performed to find out the distribution and direction of potential groundwater pollution. Nitrate concentration was analysed by taking 18 groundwater samples scattered in the upstream, midstream and downstream areas of the Code River. The results of this study indicate that nitrate concentrations in the water well of upstream and downstream areas could still be used as a source of drinking water and recreation-irrigation-livestock. Meanwhile, the nitrate concentration in water well of the midstream area of the Code River, Yogyakarta City, mostly (80% of the sample) did not meet all classes of water quality standards. Human activities in the densely populated settlements were the main factors that influence nitrate pollution. Furthermore, groundwater flow in the study area leads from north to south and towards the Code River. This condition indicates that the nitrate concentrations in the groundwater can be a source of a pollutant for the Code River.